2015
DOI: 10.1111/2047-3095.12100
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Attitudes Toward NANDAI Nursing Diagnoses: A Cross‐Sectional Study of Jordanian Nursing Students

Abstract: Proper implementation of NANDA-I is a prerequisite to the better understanding of nursing language.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
2
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 28 publications
4
14
2
11
Order By: Relevance
“…The latter study revealed that most nursing diagnoses were not written according to the NANDA-I. The high compliance with NANDA-I in our study supports the results of a previous study within the Jordanian context, where nursing students showed a positive attitude toward using NANDA-I nursing diagnosis [17]. Further, this could be due to the emphasis placed on the concept during the intense nursing education that is continuously provided to nurses by the hospital.…”
Section: Discussionsupporting
confidence: 85%
“…The latter study revealed that most nursing diagnoses were not written according to the NANDA-I. The high compliance with NANDA-I in our study supports the results of a previous study within the Jordanian context, where nursing students showed a positive attitude toward using NANDA-I nursing diagnosis [17]. Further, this could be due to the emphasis placed on the concept during the intense nursing education that is continuously provided to nurses by the hospital.…”
Section: Discussionsupporting
confidence: 85%
“…Internalisation of the importance of correct nursing diagnoses is achieved through nursing education. A study conducted by El-Rahman et al indicated that Jordanian nursing students perceived nursing diagnoses positively (19). In a study in Turkey by Hakverdioğlu et al, most of the students stated that nursing diagnoses were a priority in care practices (20).…”
Section: Perceptions Regarding Nursing Diagnosis Of Students and The Difference Of Two Modelsmentioning
confidence: 99%
“…Another important cause that adds to this issue is inadequate knowledge of staff members about the nursing process and specific nursing diagnosis for particular disease process. This cause holds great importance to be concerned about, as nurses' self-knowledge and critical thinking is essential in providing holistic care to patients [16]. Thinking critically assure that nurse will take the best decisions for health of patients [17].…”
Section: Figure 2: Fish Bone Diagrammentioning
confidence: 99%